Genome-wide identification and evolutionary analyses of the PP2C gene family with their expression profiling in response to multiple stresses in Brachypodium distachyon. (December 2016) - Cao, Jianmei; Jiang, Min; Li, Peng; Chu, Zhaoqing
Abstract Background The type-2C protein phosphatases (PP2Cs), negatively regulating ABA responses and MAPK cascade pathways, play important roles in stress signal transduction in plants.Brachypodium distachyon is a new model plant for exploring the functional genomics of temperate grasses, cereals and biofuel crops. To date, genome-wide identification and analysis of thePP2C gene family inB. distachyon have not been investigated. Results In this study, 86PP2C genes inB. distachyon were identified. Domain-based analyses of PP2C proteins showed that they all contained the phosphatase domains featured as 11 conserved signature motifs. Although not all phosphatase domains of BdPP2C members included all 11 motifs, tertiary structure analysis showed that four residues contributing to magnesium/manganese ions (Mg2+ /Mn2+ ) coordination were conserved, except for two noncanonical members. The analysis of their chromosomal localizations showed that most of theBdPP2C genes were located within the low CpG density region. Phylogenetic tree and synteny blocks analyses amongB. distachyon, Arabidopsis thaliana andOryza sativa revealed that all PP2C members from the three species can be phylogenetically categorized into 13 subgroups (A–M) andBdPP2Cs were evolutionarily more closely related toOsPP2Cs than toAtPP2Cs . Segmental duplications contributed particularly to the expansion of theBdPP2C gene family and all duplicatedBdPP2C s evolved mainly from purifying selection. Real-time quantitative reverse transcription PCR (qRT-PCR) analysis showed thatBdPP2Cs were broadly expressed in disparate tissues. We also found that almost all members displayed up-regulation in response to abiotic stresses such as cold, heat, PEG and NaCl treatments, but down-regulation to biotic stresses such as Ph14, Guy11 and F0968 infection. Conclusions In the present study, a comprehensive analysis of genome-wide identification and characterization of protein domains, phylogenetic relationship, gene and protein structure, chromosome location and expression pattern of thePP2C gene family was carried out for the first time in a new model monocot, i.e., B. distachyon . Our results provide a reference for genome-wide identification of thePP2C gene family of other species and also provide a foundation for future functional research onPP2C genes inB. distachyon .